Provision of supportive spiritual care for hepatopancreatic cancer patients: an unmet need?. Issue 9 (September 2021) - Palmer Kelly, Elizabeth; Hyer, J. Madison; Paredes, Anghela Z.; Tsilimigras, Diamantis; Meyer, Bonnie; Newberry, Hanci; Pawlik, Timothy M.
Abstract: Background: Among patients with a serious cancer diagnosis, like hepatopancreatic (HP) cancer, spiritual distress needs to be addressed, as these psychosocial-spiritual symptoms are often more burdensome than some physical symptoms. The objective of the current study was to characterize supportive spiritual care utilization among patients with HP cancers. Methods: Patients with HP cancer were identified from the electronic medical record at a large comprehensive cancer center; data on patients with breast/prostate cancer (non-HP) were collected for comparison. Associations between patient characteristics and receipt of supportive spiritual care were evaluated within the overall sample and end-of-life subsample. Results: Among 8, 961 individuals (nHP =1, 419, nnon-HP =7, 542), 51.7% of HP patients utilized supportive spiritual care versus 19.8% of non-HP patients (p<0.001). Younger age and religious identity were associated with receiving spiritual care (p<0.001). HP patients had higher odds of receiving spiritual care versus non-HP patients (OR 2.41, 95%CI: 2.10, 2.78). Within the end-of-life subsample, HP patients more frequently received spiritual care to "accept their illness" (39.5% vs. 22.5%, p<0.001), while non-HP patients needed support to "define their purpose in life" (13.1% vs. 4.5%, p=0.001). Discussion: Supportive spiritual care was important to a large subset of HP patients and should be integrated into their care.